Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Information Asymmetry dengan Variabel Kontrol Volatilitas Arus Kas dan Profil Industri - Angelina Evelyn; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
The affect of corporate social responsibility (CSR) on information asymmetry had been poorly invesetigated. However, there were only a few studies about the affect of CSR on information asymmetry. The aimed of this research was to examine the affect of CSR toward information asymmetry which measured by bid ask spread.Corporate social responsibility measured by using corporate social responsibility disclosure level that assessed by using criteria guideliness of GRI. The information asymmetry was measured by using bid ask spread. This study also used control variables of volatility cash flow and profile industry. This research was carried out on go public companies in Indonesia which published sustainability report and listed in GRI’s database with a sample of 130.The results of this study showed that there was reciprocal relationship between corporate social responsibility and information asymmetry. The control variables of volatility cash flow had positive affect on information asymmetry, while industry profile had no affect on information asymmetry.